2006
DOI: 10.1111/j.1442-2042.2006.01240.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the effectiveness and side‐effects of tolterodine and oxybutynin in children with detrusor instability

Abstract: Background : Treatment with anticholinergic agents is the mainstay of therapy for detrusor instability (DI), a chronic and morbid condition characterized by urge urinary incontinence. The aim of this study is to assess the effectiveness and tolerability of tolterodine and oxybutynin in children with DI. Methods : A total of 60 children with DI were enrolled, 30 (14 male, 16 female, mean age 7.97 ± 2.71 years) in the tolterodine group and 30 (12 male, 18 female, mean age 7.33 ± 2.23 years) in the oxybutynin gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(7 citation statements)
references
References 14 publications
1
6
0
Order By: Relevance
“…Previous studies have suggested that SB consumption may contribute to ADHD symptoms and childhood hyperactivity …”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have suggested that SB consumption may contribute to ADHD symptoms and childhood hyperactivity …”
Section: Discussionmentioning
confidence: 99%
“…reported oral administration of SB for four weeks induced anxiety and motor impairment in rats ( 38 ). Furthermore, human studies in the context of the effects of SB suggested that high intake of SB may be associated with attention deficit hyperactivity disorder (ADHD) and hyperactivity in children, but this needs to be further investigated ( 39 40 41 ).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study comparing the efficacy and tolerability of oxybutynin IR and tolterodine IR in 60 children with DO showed similar efficacy but significantly fewer total AEs in children treated with tolterodine IR (13 vs 27 AEs). Eight children (27%) who were initially randomized to oxybutynin IR treatment crossed over to tolterodine IR because of AEs [197]. In a combined analysis of two placebo‐controlled studies of tolterodine ER in children aged 5–10 years with incontinence suggestive of DO, changes in incontinence episodes per week, micturitions per 24 h, and urine volume per micturition with active treatment did not differ significantly from placebo.…”
Section: Tolerability and Safetymentioning
confidence: 99%